Effect of Dietary Amylose/Amylopectin Ratio on Intestinal Health and Cecal Microbes’ Profiles of Weaned Pigs Undergoing Feed Transition or Challenged With Escherichia coli Lipopolysaccharide - Yang, Can; Wang, Min; Tang, XiaoWu; Yang, HuanSheng; Li, FengNa; Wang, YanCan; Li, Jianzhong; Yin, YuLong (Frontiers in Microbiology, 2021)
Background Dietary amylose/amylopectin ratio (DAR) plays an important role in piglets’ intestinal health. It is controversial whether diarrhea could be relieved by changing DAR in weaning piglets. Methods Sixty (Landrace × Yorkshire) castrated male pigs (initial body weight (BW) 6.51 ± 0.64 kg) were randomly allocated to five groups (one pig per cage and 12 replicates per group) according to their BW. Piglets received diets with different DARs (0.00, 0.20, 0.40, 0.60, and 0.80) for 29 days. Feed transition occurs at day 15. The piglets were challenged with lipopolysaccharides (Escherichia coli LPS, 100 μg/kg BW) on day 29 by intraperitoneal injection at 12 h before slaughter. Chyme was collected for pH value, short-chain fatty acid (SCFA), and cecal microbe analysis using 16S rRNA gene sequencing; mucosa was sampled for detecting gene expression. Results Rate and degree of diarrhea were higher when DAR was 0.40 than when it was 0.20 and 0.80 during the third week (P < 0.05). The chyme pH value in the cecum was higher (P < 0.05) in 0.20 DAR than in 0.00 and 0.80 DARs, but with no significant difference compared with 0.40 and 0.60 DARs (P > 0.05). Cecal isobutyric acid and isovaleric acid concentrations were higher in 0.20 than in other groups (P < 0.01). Cecal SCFAs such as acetic acid, propionic acid, and total SCFA, concentrations were higher in 0.40 DAR than in 0.00, 0.60, and 0.80 DARs (P < 0.05), but with no significant difference when compared with 0.20 (P > 0.05). Cecal crypt depth was lower (P < 0.05) in 0.80 than in other groups, but not 0.40. Claudin mRNA expression in the mucosa of the ileum was higher in 0.20 than in other groups (P < 0.01). The alpha diversity of cecal microbe representative by goods coverage was higher in group 0.40 when compared with group 0.20 (P < 0.05). At the genus level, the abundances of the Ruminococcaceae_NK4A214_group and Anaerotruncus were higher but that of Cetobacterium was lower in the cecal chyme of group 0.20 than that of group 0.60 (P < 0.05), with no significant difference compared with other groups (P > 0.05). The diarrhea rate during the third week was negatively correlated with the abundances of Rikenellaceae_RC9_gut_group and X.Eubacterium_coprostanoligenes_group (P < 0.05). Conclusion Compared with diet high in amylose or amylopectin, diet with DAR 0.40 showed a worse degree of diarrhea in weaned piglets during feed transition. But the intestinal health will be improved the week after the microbes and metabolites are regulated by DAR.